The geriatric syndrome of sarcopenia impacts allogeneic hematopoietic cell transplantation outcomes in older lymphoma patients. Issue 8 (2nd July 2020) - Lin, Richard J.; Michaud, Laure; Lobaugh, Stephanie M.; Nakajima, Reiko; Mauguen, Audrey; Elko, Theresa A.; Ruiz, Josel D.; Maloy, Molly A.; Sauter, Craig S.; Dahi, Parastoo B.; Perales, Miguel-Angel; Shah, Gunjan L.; et al.
Abstract: Older patients with advanced hematologic malignancies are increasingly considered for allogeneic hematopoietic cell transplantation (allo-HCT) yet their survival outcomes remain suboptimal. We and others have previously shown that pre-HCT multi-morbidity and functional limitation and post-HCT geriatric syndromes significantly impact outcomes. Sarcopenia, an accelerated loss of muscle mass and function, has been increasingly recognized in older cancer patients. We identified 146 lymphoma patients 50 years or older who were allografted from 2008 to 2018 at our institution and found that before allo-HCT, 80 (55%) patients were sarcopenic. Pre-HCT sarcopenia was significantly associated with overall survival, progression-free survival, and nonrelapse mortality independent of multi-morbidity and functional limitation. In 6-month landmark analysis, post-HCT sarcopenia remained significantly associated with survival. Our findings illustrate the high prevalence and profound impact of sarcopenia on survival. While requiring prospective confirmation, preemptive, longitudinal, and multidisciplinary interventions for sarcopenia are warranted to improve HCT outcomes for older patients.